La extranjería como extimidad: Más al sur de Paloma Vidal - Seifert, Marcos Germán (2014)
In the stories that comprise Paloma Vidal’s book Más al sur (2011) we find a variety of characters in transit who speculate about their status as foreigners. Their foreignness is not presented only as an identity’s destabilization, but also it is proposed as a way of inadequacy respect to memory and inheritance. This foreingnness allows us to think a space that combines both alienation and belonging in cultural, linguistic and family dimensions. The term extimacy is relevant to understand this position because it refers to an intimacy that has a quality of exteriority.